The Impact of Credit Rating Changes on CDS Spreads - Klinge, Johanna (My University, 2018)
Only a few papers have studied the impact of credit rating announcements on CDS spreads. The first papers were published in 2004. This thesis studies if the credit rating changes of the well-known S&P 500 firms have an impact on the CDS spreads before, around and after the rating changes. This thesis investigates rating classes also separately. The investigated time period covers the period after the financial crisis of 2008. It is a period of exceptionally low interest rates and steady climb of S&P 500 index. The results cover the eight-year long time period from 2009 to 2016. This thesis uses CDS data for the S&P 500 firms, and credit rating data for rating agencies Standards & Poor’s and Moody’s. The relationship is studied using an event study methodology. The results show that the CDS market anticipates downgrades at some level. The CDS spread reacts already 90 days before a downgrade by S&P. For upgrades, the CDS market does not anticipate the rating changes. There is a clear announcement day effect around downgrades, but around upgrades it is not so clear. There are no post-announcement day effects after rating changes. The impact of downgrades on CDS spreads is greater than the impact of upgrades. This thesis has equal numbers of downgrades and upgrades which shows that the difference is real and not an effect of different sizes of the populations.
Keywords: CDS spread; credit rating; rating changes; downgrades; upgrades; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|